2020
DOI: 10.5114/ppn.2020.100036
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress, inflammation and glial cell in pathophysiology of myofascial pain

Abstract: Purpose: The aim of this article is to explain the role of oxidative stress, inflammatory responses, and glial cell in the pathophysiology of myofascial pain. Therefore the management of myofascial pain can be optimally done by clinicians through blockage of each biomarker in a specific pathway. Views: Myofascial pain is often one of the reasons for patients to visit the doctor with a prevalence of approximately 21-30%. Overused muscle can lead to myofascial trigger points. Activities that cause ongoing muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…36 Widyadharma in his review suggested that alterations in astrocyte activation and reactive astrogliosis are sufficient in MTrPs creation. 37 Models used by Álvarez et al were previously described as fibromyalgia pain models. 26 In human studies, there was a confirmation that conditions like fibromyalgia are said to have greater comorbidity, eg higher number of MTrPs.…”
Section: Involvement Of Cnsmentioning
confidence: 99%
“…36 Widyadharma in his review suggested that alterations in astrocyte activation and reactive astrogliosis are sufficient in MTrPs creation. 37 Models used by Álvarez et al were previously described as fibromyalgia pain models. 26 In human studies, there was a confirmation that conditions like fibromyalgia are said to have greater comorbidity, eg higher number of MTrPs.…”
Section: Involvement Of Cnsmentioning
confidence: 99%